Brain and Pituitary Response to Vaccination in Gilthead Seabream (Sparus aurata L.) - Liu, X. H.; Khansari, A. R.; Teles, M.; Martínez-Rodríguez, G.; Zhang, Y. G.; Mancera, J. M.; Reyes-López, F. E.; Tort, L. (Frontiers in Physiology, 2019)
Vaccination is a widely used therapeutical strategy in aquaculture, but whether vaccination elicits stress responses in the central neuroendocrine system and enhances the crosstalk between the immune and endocrine systems in the brain or pituitary after vaccination is unclear. To answer this question two experiments using two different vaccine exposure routes, i.e., bath or intraperitoneal (i.p.) injection, were carried out on gilthead seabream (Sparus aurata L.). In the first one, the stress responses of fish subjected to waterborne Vibrio anguillarum bacterin were compared with responses after air exposure or their combination. In the second experiment, fish were subjected to an intraperitoneal injection of Lactococcus garvieae bacterin and we assessed the central stress response and also whether or not a significant immune response was induced in brain and pituitary. In both experiments, blood, brain and pituitary tissues were collected at 1, 6, and 24 h post stress for plasma hormone determination and gene expression analysis, respectively. Results indicated that bath vaccination induced a decreased central stress response compared to air exposure which stimulated both brain and pituitary stress genes. In the second experiment, injection vaccination kept unchanged plasma stress hormones except cortisol that raised at 6 and 24 h. In agreement, non-significant or slight changes on the transcription of stress-related genes were recorded, including the hormone genes of the hypothalamic pituitary interrenal (HPI) axis and other stress markers such as hsp70, hsp90, and mt genes in either brain or pituitary. Significant changes were observed, however, in crhbp and gr. In this second experiment the immune genes il1β, cox2, and lys, showed a strong expression in both brain and pituitary after vaccination, notably il1β which showed more than 10 fold raise. Overall, vaccination procedures, although showing a cortisol response, did not induce other major stress response in brain or pituitary, regardless the administration route. Other than main changes, the alteration of crhbp and gr suggests that these genes could play a relevant role in the feedback regulation of HPI axis after vaccination. In addition, from the results obtained in this work, it is also demonstrated that the immune system maintains a high activity in both brain and pituitary after vaccine injection.